Investigation of the fatigue characteristics of warm stone matrix asphalt (WSMA) containing electric arc furnace (EAF) steel slag as coarse aggregate and Sasobit as warm mix additive. (December 2019) - Alinezhad, Mojtaba; Sahaf, Ali
Highlights: In this research, a part of natural coarse aggregates was replaced with EAF slag. Warm mix asphalt technology (Sasobit) was employed to produce warm SMA mixture. Fatigue characteristics of WSMA mixture were determined using flexural fatigue test. EAF steel slag indicated great potential to substitute for natural aggregates. Warm SMA showed weaker but acceptable fatigue performance compared to the SMA mix. Abstract: On the one hand, several million tons of steel slag is produced annually as the by-product of the steel industry in Iran and other countries and are deposited in landfills without any use, occupy vast areas, and cause environmental hazards. On the other hand, the high mixing temperature of the hot mix asphalt (HMA) increases the emission of greenhouse gases, the cost of fuel, accelerated wear of asphalt plant equipment, and less safety of workers in the field. These kinds of problems challenge the use of HMA mixtures and encourage to investigate more the WMA technology. This research intends to investigate the fatigue characteristics of warm stone matrix asphalt (WSMA), as one of the significant structural distresses of the flexible pavements, containing EAF steel slag as part of the coarse aggregate and Sasobit as the warm mix additive. The Marshal test results indicated higher Marshall stability and Marshal quotient for mixtures containing EAF steel slag compared to their similar mixtures (SMA + S vs SMA + N and WSMA + S vs WSMA + N) and all the mixtures met the NAPA specification requirements for Marshall stability, air voids, and optimum binder content. The result of draindown test for all of the mixtures was lower than the maximum amount determined by the specifications and means that the rock wool fibers, as asphalt stabilizers, preserved the asphalt mortar in the mixture well. The fatigue test results indicated that the use of EAF slag leads to comparable results to standard SMA and using warm mix additive (Sasobit) results in lower but acceptable results.